Optimization of Workstation Capacity using the Theory of Constraints Approach to Increase Production Output - Putri, Fadilla Umeida; Aryanny, Enny (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
A manufacturing company in Surabaya that produces various metal-based products is facing bottleneck issues, particularly in the production of steel doors and fire doors, due to an imbalance in machine capacity and cycle time. This problem has led to an accumulation of semi-finished goods and a decline in production efficiency. To address this issue, this study applies the Theory of Constraints (TOC) to redesign production planning through five key stages. Based on Rough-Cut Capacity Planning (RCCP) calculations, bottlenecks were identified at the bending workstation (SK-2), assembly workstation (SK-3), and painting workstation (SK-5). To mitigate these constraints, an additional 7 hours of overtime was implemented at these three workstations from July to November 2024. This strategy successfully increased fire door production from 89 units with a throughput of Rp178,000,000 to 167 units with a throughput of Rp334,000,000, reflecting a growth of Rp156,000,000 (46.7%). These findings demonstrate that the proposed approach is effective in optimizing throughput and maximizing production capacity utilization.